MU’ARADHAH DALAM SISTEM DEMOKRASI MULTI PARTAI MENURUT PEMIKIRAN YUSUF AL-QARADHAWI - Fikri Afdhal; Mutiara Fahmi; Boihaqi Bin Adnan (Journal of Indonesian Comparative of Syari'ah Law, 2025)
In modern democratic practice, opposition is often perceived as a threat to political stability, especially in Muslim-majority countries. However, in the context of contemporary Islamic thought, opposition holds its own legitimacy. This study explores how Yūsuf al-Qaraḍhāwī conceptualizes mu‘āraḍhah (opposition) within a multi-party democratic system. The purpose of this research is to analyze al-Qaraḍhāwī’s perspective on political opposition as a means of controlling power in accordance with Islamic law. This study employs a library research method using a qualitative-descriptive approach by examining al-Qaraḍhāwī’s works and related literature. The findings reveal that, according to al-Qaraḍhāwī, mu‘āraḍhah is not a form of rebellion against the ruler, but rather a legitimate form of political participation that fulfills the Islamic obligation of enjoining good and forbidding evil (amr bi al-ma‘rūf wa nahy ‘an al-munkar), while preventing abuse of power. A multi-party system that accommodates peaceful opposition is compatible with Islamic values, provided it is constructive, avoids slander, and does not cause division among the Muslim community. Therefore, the concept of mu‘āraḍhah should be developed as a shar‘ī mechanism to balance authority and political morality in the framework of Islamic democracy.